Corporate Governance of Banks, The Key for Trust: A Bibliometric Analysis - Banu Sultanoğlu; Burcu Gurol; Gerçek Özparlak (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Corporate governance aims to create a transparent, fair, accountable, and responsible management environment for all stakeholders. Due to the significant role of banks in the economy, corporate governance in banks is indispensable for establishing trust, which is crucial for them to survive. Albeit numerous bibliometric analyses have been found solely on banks or corporate governance, there needs to be more bibliometric analysis on the corporate governance of banks. Thus, this study aims to explore the research works of corporate governance, particularly of banks, by conducting a bibliometric analysis from 2003 to 2022. The results show that the interest in corporate governance in banks increased, especially after the 2008 financial crisis, and the studies focused on the board structure-bank performance and board structure-risk appetite relations. Additionally, corporate governance has emerged as an essential topic in Islamic banking since the 2010s.